Development of QR Code Labeling Application for Fixed Asset Accounting Information System in Mangimbali Group with Minimalist Development Techniques - Heidy Pesik; Kiet Tumiwa; Edwin Edwin; Lumunon Lumunon (Jurnal Indonesia Sosial Teknologi, 2024)
Mangimbali Group is a distributor company engaged in the retail of lubricants for Pertamina and supports construction work and the procurement of equipment for Pertamina Geothermal. Mangimbali Group has several entities, namely PT. Mangimbali Peluas Jaya and PT. Cipta Jaya Perkasa. The opening of two entities certainly requires a large flow of capital, so one of the management policies is to make one office building for two entities but all assets are still separated. This requires a good Fixed Asset Management Accounting System for the distribution of Fixed Assets. Fixed Assets that have been purchased if the inventory system is not properly regulated can cause losses for the company in the form of loss of Fixed Assets. Also for easy tracking of assets in the same building with the ownership of different entities. The purpose of this study is to design a fixed asset accounting information system application using QR codes to improve the efficiency and accuracy of bookkeeping inventory and being able to store more comprehensive data on fixed asset data in each entity. The research method applied is a software development method by Prototyping where the software creation process will be carried out module by module with testing, starting from tagging and creating a unique QR code for each fixed asset on each existing entity. In addition, the development process is taken with minimalist techniques. Especially in the creation of models and the number of databases and tables.